Niger : Request for a Three-Year Arrangement Under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Niger. (IMF Staff Country Reports; Country Report ;, 2021)
Niger's new government developed an ambitious reform agenda in the face of daunting challenges. The previous ECF-supported program was able to preserve macroeconomic stability and implement some key PFM reforms, notwithstanding the pandemic. However, progress on revenue mobilization was more limited, reflecting capacity constraints and a challenging environment. For the new government to achieve its development goals, it will have to overcome deep-seated social and political divisions and a deteriorating regional security situation. Enhanced reforms and the advent of oil exports over the medium-term offer hope that greater domestic resources can be marshalled to accelerate growth and poverty reduction.